Sistem Monitoring dan Pengontrolan Aquascape Tanaman Anubias dan Cuba menggunakan Metode Fuzzy - Rizky Putra Wijaya; Dahnial Syauqy; Muhammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Aquascape is one of the artificial water ecosystem, the aquascape system is mutually benefical. There are two important elements in this system, these two elements are bacteria and plants. In an aquascape, the water acidity (pH) and water level are important parameters that must be controlled and maintained to make aquascape can grow optimally, with this being the case, need control system by implementing the fuzzy method as a data processor and decision maker of water pH and water level. The next step is processing the pH and the water level on Arduino Uno microcontroller. The fuzzy membership is obtained from input of questionnaire responder, then data is used for implication process using the min function, next process is compossition. On compossition proccess, function used is the max function. Next proccess is interference process, and the last process is defuzzification process to get a firm value as the duration of the pump. In testing each sensor, the pH sensor and ultrasonic sensor have been running with a low error rate. In testing the methodology, Mamdani fuzzy method, the test is comparing manually output from the Mamdani fuzzy with manual calculation.based on the data obtained, the comparison between results of the system and manual calculation has the same output, based on these result, it can be concluded that system is in accordance with fuzzy calculation, and has a low error rate.